ASH-SHIDDIQ GREAT MOSQUE AT NGAMPRAH WEST BANDUNG REGENCY - Satya Wirawan, Arif
The Ash-shiddiq Great Mosque is a procurement project of regency/city scale facilitiy conducted by West Bandung Regency government. The mosque is located in Ngamprah District, in the office complex of West Bandung Regency government. This mosque will be used by the Ngamprah District society and also the government office employees. One of the points in the client's vision is to make the society become more religious. This makes the Ash-Shiddiq Great Mosque should be able to bring the society of West Bandung Regency in general and Ngamprah District in particular closer to Islam. The functions that are accomodated within this mosque, besides the function of worship, are also social and economic functions as a respond to the user and the context of the building. The majority of the society work as a merchant so the facility should be able to accommodate such trading activities. The purpose of this project is to design a mosque that can be part of the society. This mosque should be able to accommodate all of the society activities so that will make this mosque become more vital to the society. That is because today, many mosques are visited only to perform the ritual worship only, while mosque is originally a center of community activities that can be used to conduct various activities. Mosque as a public space is chosen as the concept of the mosque so it can be what a mosque should be, as a public space and the center of its community activities.